The Relations between Science and Politics in Social Philosophy of J. Habermas - Gedutis, Aldis (Problemos, 2001)
The article analyses Jügen Habermas’ attitude towards relations between science and politics, and influence of science upon political sphere. The author seeks to figure out the following: in what ways, according to Habermas, science could be dangerous for social life; then, Habermas’ position concerning validity of the main charges raised against science. Finally the author discusses alternative version of science and its sociopolitical role proposed by Habermas.
Keywords: Habermas; science; politics; ideology; instrumental and communicative rationality